Effectiveness of agalsidase alfa enzyme replacement in Fabry disease: cardiac outcomes after 10 years' treatment. Issue 1 (December 2015) - Kampmann, Christoph; Perrin, Amandine; Beck, Michael
Abstract Background To explore long-term effects of agalsidase alfa on Fabry disease cardiomyopathy in adults. Methods Retrospective analysis of prospectively collected data at a single center in Mainz, Germany, revealed that 45 adult patients (21 men, 24 women) had received agalsidase alfa for approximately 10 years. Data were extracted for cardiac and heart failure status, echocardiographic evaluations of cardiac structure and function, and renal function at treatment start and during agalsidase alfa treatment. Results After 10 years of agalsidase alfa treatment, heart failure classification had improved by at least 1 class in 22/42 patients, and angina scores were stable or improved in 41/42 patients. During treatment, no patients without left ventricular hypertrophy (LVH) at treatment initiation developed LVH, and no patients with LVH at treatment initiation showed a decline in left ventricular mass. Conclusions Approximately 10 years of agalsidase alfa treatment appeared to have beneficial effects for controlling progression and improving some symptoms of Fabry-associated cardiomyopathy.